Struktur, Sifat Dielektrik dan Optik Senyawa Aurivillius (Ca0,5Ba0,5)Bi4Ti4O15 yang Disintesis dengan Teknik Lelehan Garam - Silvi Veronita; Upita Septiani; Zulhadjri Zulhadjri (Jurnal Riset Kimia, 2022)
Synthesis of ferroelectric material based onAurivillius phases, (Ca0.5Ba0.5)Bi4Ti4O15 (CBBT), have been done using a molten salts technique.The results of X-ray diffraction (XRD) analysis showed the characteristic peaks at 2θ = 12.93°, 17.31°, 21.64°, 23.23°, 27.71°, 30.33°, and 32.90° which was correspond to the four-layers of Aurivillius phase.Refinement structure using the Le Bail method, the sample is suitable for orthorhombic structures with the A21am space group. The orthorhombicity of the CBBT is small and nearer to tetragonal symmetry.Fourier Transform Infra-red (FTIR) spectra show distortion of TiO6 octahedral at 847 cm-1 and strain vibrations of TiO6 octahedra at 545 cm-1 due to A-O bonds.Analysis using Scanning Electron Microscopy (SEM) shows the morphology of the sample in the form of plate-like which is characteristic of Aurivillius phase.The ferroelectric to paraelectric phase transition temperature (Tc) was obtained at 635ºC.The band gap value of the CBBT compound was 3.17 eV, relatively the same with the CaBi4Ti4O15 (CBT) compound.